VADSTENA CARE CROSS - GYDELL, KARL-JOHAN; KUKLINSKA, ALEKSANDRA; VAN LAETHEM, FLORENCE (My University, 2023)
TASK The focus of the autumn 2022 Chalmers Healthcare Studio was to design a primary care centre in Vadstena municipality. The task focused on the contemporary context of Nära vård in Sweden. With this new focus, primary care centers will play an important role in reducing the pressure on big hospitals but they will also act as preventive care facilities located closer to inhabitants. This means that the primary care centre should serve as a community health centre, where the patients have a proactive role. The studio was collaborating with a real client from Region Östergötland to create different proposals for a new building for the primary health facility in Vadstena. SITE Vadstena is a municipality located in southeast Sweden in Östergötland County with 7.400 inhabitants. The requested project brief contains 3.000 square metres including the following departments: primary care unit, specialist outpatient unit, public dental care, child care and a family centre. In the current primary care centre in Vadstena 7.500 patients are listed and the building is not suited for the modern standards of healthcare.Vadstena has a long tradition connected to healthcare since the 15th century. The site of the project is located in the Brigitta's Hospital area which was build from 1947-1961. One of the existing building in the project site has an important heritage value and needs to be preserved (B), while the other one can be demolished (C). The design of the site also includes the Brigitta Square (A) which these days is not defined and works mostly as a parking lot. PROJECT The design of the project focused on a high level of standardization of the floor plans and optimization of the patient & staff flows. Special attention was made on patient safety and easy wayfinding. In this project, creating a future proof primary care center was of utter importance.